Determinants of Postpartum Visits in Breastfeeding Mother - Eny Retna Ambarwati; Endang Khoirunnisa; Triantoro Safaria (International Journal of Public Health Science (IJPHS), 2016)
Puerperal is likely in the occurrence of maternal deaths, and should receive health care during childbirth to be visited by a health worker at least 3 times since birth. This type of research was descriptive quantitative. The quantitative data obtained from questionnaires, using T-test. The research sample was breastfeeding mothers in the village of Balecatur as the intervention group and breastfeeding mothers in the village of Ambarketawang as the control group. There are significant differences of knowledge, behavior in the treatment of post-partum mothers between the intervention group and the control group with significant value in total of <0.05, influenced by the role of cadres, social suport, the role of health workers. Post partum visits conducted by community empowerment strategies, women as the main actors. The role of leaders, social support affect the success of efforts to increase postnatal visits among others disseminating information, provide examples, sensitize, motivate, guide, moving targets and the community and facilitating thus the knowledge, skills and increased public awareness can foster public participation in the postnatal visit.